Yi-Zhi-Fang-Dai Formula Exerts a Protective Effect on the Injury of Tight Junction Scaffold Proteins in Vitro and in Vivo by Mediating Autophagy through Regulation of the RAGE/CaMKKβ/AMPK/mTOR Pathway - Chan, Yuanjin; Chen, Wenjing; Chen, Yanjie; Lv, Zhongkuan; Wan, Wenbin; Li, Yaming; Zhang, Chunyan (Biological & pharmaceutical bulletin, 2020)
Alzheimer’s disease (AD) is a chronic neurodegeneration disease that is closely related to the abnormal tight junction scaffold proteins (TJ) proteins of the blood–brain barrier (BBB). Recently, Yi-Zhi-Fang-Dai Formula (YZFDF) had exerted a neuronal protective effect against amyloid peptide (Aβ) toxicity. Still, the therapeutic mechanism of YZFDF in restoring Aβ-induced injury of TJ proteins (ZO-1, Occludin, and Claudin-5) remains unclear. This study aimed to explore the underlying mechanism of YZFDF in alleviating the injury of TJ proteins. We examined the impacts of YZFDF on autophagy-related proteins and the histopathology of Aβ in the APP/PS1 double-transgenic male mice. We then performed the free intracellular calcium levels [Ca2+]i analysis and the cognitive behavior test of the AD model. Our results showed that YZFDF ameliorated the injury of TJ proteins by reducing the mRNA transcription and expression of the receptor for advanced glycation end-products (RAGE), the levels of [Ca2+]i, calmodulin-dependent protein kinase β (CaMKKβ), phosphorylated AMP-activated protein kinase (AMPK). Accordingly, YZFDF increased the expression of the phosphorylated mammalian targets of rapamycin (mTOR), leading to inhibition of autophagy (downregulated LC3 and upregulated P62). Moreover, the Aβ1–42 oligomers-induced alterations of autophagy in murine mouse brain capillary (bEnd.3) cells were blocked by RAGE small interfering RNA (siRNA). These results suggest that YZFDF restored TJ proteins’ injury by suppressing autophagy via RAGE signaling. Furthermore, YZFDF reduced the pathological precipitation of Aβ in the hippocampus, and improved cognitive behavior impairment of the AD model suggested that YZFDF might be a potential therapeutic candidate for treating AD through RAGE/CaMKKβ/AMPK/mTOR-regulated autophagy pathway.